2022
DOI: 10.1111/ijsw.12551
|View full text |Cite
|
Sign up to set email alerts
|

Effect of financial services access on health services utilisation among rural older adults in Ghana

Abstract: This study explored the effect of access to financial services on rural older adults' health services utilisation. A cross‐sectional survey design was adopted to gather data (N = 310; mean age = 66.13 years and standard deviation [SD] = 24.72) in selected rural communities in Ghana. We applied endogenous treatment Poisson regression (ETPR), an econometrics model that accounts for self‐selection bias, to estimate the association between access to financial services and the use of health services. Findings revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…For instance, our analysis showed that age, education level, employment status, health insurance enrollment and self-rated health of caregivers predicted healthcare utilization. This is consistent with previous studies that have established that age [ 47 ], education [ 37 , 45 ], employment [ 93 , 94 ], health insurance enrollment [ 51 , 95 ] and self-rated health [ 76 ] are associated with healthcare utilization.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…For instance, our analysis showed that age, education level, employment status, health insurance enrollment and self-rated health of caregivers predicted healthcare utilization. This is consistent with previous studies that have established that age [ 47 ], education [ 37 , 45 ], employment [ 93 , 94 ], health insurance enrollment [ 51 , 95 ] and self-rated health [ 76 ] are associated with healthcare utilization.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, our outcome variable was healthcare utilization. Healthcare utilization was defined as seeking treatment from a formal healthcare provider (including public/private hospitals, clinics, and health centres) [ 18 , 45 47 , 51 , 76 ], and an informal healthcare provider (such as over-the-counter medication, salespeople, drug peddlers, traditional treatment/unlicensed practitioners, paraprofessional, and self-care treatment) [ 51 ] over the last one year preceding the survey. The one-year estimation rate of healthcare utilization in this study is consistent with earlier published works [ 45 47 , 51 , 77 , 78 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations